Biophysical defects of an SCN5A V1667I mutation associated with epinephrine‐induced marked QT prolongation. (2nd June 2020) - Nakajima, Tadashi; Dharmawan, Tommy; Kawabata‐Iwakawa, Reika; Tamura, Shuntaro; Hasegawa, Hiroshi; Kobari, Takashi; Kaneko, Yoshiaki; Nishiyama, Masahiko; Kurabayashi, Masahiko
Abstract: Background: The epinephrine infusion test (EIT) typically induces marked QT prolongation in LQT1, but not LQT3, while the efficacy of β‐blocker therapy is established in LQT1, but not LQT3. We encountered an LQT3 family, with an SCN5A V1667I mutation, that exhibited epinephrine‐induced marked QT prolongation. Methods: Wild‐type (WT) or V1667I‐SCN5A was transiently expressed into tsA‐201 cells, and whole‐cell sodium currents ( I Na ) were recorded using patch‐clamp techniques. To mimic the effects of epinephrine, I Na was recorded after the application of protein kinase A (PKA) activator, 8‐CPT‐cAMP (200 μM), for 10 minutes. Results: The peak density of V1667I‐ I Na was significantly larger than WT‐ I Na (WT: 469 ± 48 pA/pF, n = 20; V1667I: 690 ± 62 pA/pF, n = 19, P  < .01). The steady‐state activation (SSA) and fast inactivation rate of V1667I‐ I Na were comparable to WT‐ I Na . V1667I‐ I Na displayed a significant depolarizing shift in steady‐state inactivation (SSI) in comparison to WT‐ I Na ( V 1/2 ‐WT: −88.1 ± 0.8 mV, n = 17; V1667I: −82.5 ± 1.1 mV, n = 17, P  < .01), which increases window currents. Tetrodotoxin (30 μM)‐sensitive persistent V1667I‐ I Na was comparable to WT‐ I Na . However, the ramp pulse protocol (RPP) displayed an increased hump in V1667I‐ I Na in comparison to WT‐ I Na . Although 8‐CPT‐cAMP shifted SSA to hyperpolarizing potentials in WT‐ I Na and V1667I‐ I Na to the same extent, it shifted SSI to hyperpolarizing potentials much less in V1667I‐ I Na than in WT‐ I Na ( V 1/2 ‐WT: −92.7 ± 1.3 mV, n = 6; V1667I: −85.3 ± 1.6 mV, n = 6, P  < .01). Concordantly, the RPP displayed an increased hump in V1667I‐ I Na, but not in WT‐ I Na . Conclusions: We demonstrated an increase of V1667I‐ I Na by PKA activation, which may provide a rationale for the efficacy of β‐blocker therapy in some cases of LQT3.